Yield Spreads, The Exchange Rate, and Recession Predictability for Northern Mexico Border Economies - Jr, Thomas M. Fullerton; Rojo, Laura M. Saenz (Asian Journal of Economic Modelling, 2018)
Prior research suggests that the yield spread between long-term and short-term interest rates contains information regarding the likelihood of future recessions. Linkages between the yield spread and regional business cycles in emerging economies have, to date, received little attention. This study employs yield spreads for Mexico and for the United States, as well as a real exchange rate index, as potential predictors of recessions in eight metropolitan economies located in northern Mexico. The results suggest that, in most cases, the United States yield spread provides early warning signals of potential economic downturns, as does the real exchange rate index.